Answer:
Equivalent equation: x = -1/16 (y - 2)² + (-1)
Which is not equal to x = 1/16 (y - 2)² + (-1)
Step-by-step explanation:
The given equation is
y² + 16x - 4y = -20
To know if is equivalent to x = 1/16 (y - 2)² + (-1), we need to have the x on one side and the y on the other, so subtract 16x from both sides
y² + 16x - 4y - 16x = -20 - 16x
y² - 4y = -16x - 20
Then, we need to complete the square on the left side. So, we need to add (b/2)² on both sides, where b is the number besides y.
(b/2)² = (-4/2)² = (-2)² = 4
By adding 4 to both sides, we get
y² - 4y + 4 = -16x - 20 + 4
(y - 2)² = -16x - 16
Factorize -16 from the right side
(y - 2)² = -16(x + 1)
Divide both sides by (-16)
Finally, subtract 1 from both sides
Therefore, the equation is
x = -1/16 (y - 2)² + (-1)
We can see that it doesn't match the equation x = 1/16 (y - 2)^2 + (-1) because the sign of 1/16